THE RESILIENCE OF BIRD SPECIES IN A BRAZILIAN ATLANTIC FOREST REMNANT IN THE FACE OF ACCELERATED EXTINCTIONS IN THE NEOTROPICS - Cavarzere, Vagner [UNESP]; Schunck, Fabio; Mix, Peter; Donatelli, Reginaldo J. [UNESP] (IUCN, 2024)
The Caetetus Ecological Station is located in south-eastern Brazil. It is a unique protected area given it was set aside for preservation in the early 1930s, when all surrounding forests were clear-cut. Because the birds of this area have been inventoried on a number of occasions since the late 1970s, Caetetus represents a singular case study to evaluate how the bird communities have changed over time in a relatively small (2,178-ha) but intact site. We searched the literature, ornithological platforms data and included our unpublished surveys to compile ornithological records. From the 184 species initially reported, all but two appear to be still present. Unlike other well-studied forest fragments in the Neotropics, where between 10–27 per cent of all forest bird species are suggested to have become locally extinct, Caetetus stands out as a notable exception. We suggest that, based on all available evidence for other similar forests, Caetetus’ long-standing undisturbed status could be the main driver for this persistence of species. However, it is uncertain how bird species will be affected by fragmentation and species relaxation in the long term, and how they will respond to climate change. The ability to access citizen science records on public databases makes current and future tracking of species persistence much easier and more comprehensive.
Keywords: avian communities; Caetetus Ecological Station; historical records; literature review; ornithological platforms; seasonal semideciduous forests